Virtual reality learning kit for road crossing safety - Mohamad Sharif, Muhammad Fahmi; Mohamad, Shamsul; M.M, Mahadzir (2024)
The Virtual Reality Learning Kit for Road Crossing Safety project commenced with the factors contributing to pedestrian vulnerability. This analysis guided the design of the Virtual Reality (VR) Learning Kit, which combined immersive VR technology, interactive scenarios, and gamified learning elements to simulate real-life road-crossing situations. The VR kit aims to enhance road crossing skills and promote safer behaviour. 11 participants took part in a test run of the VR kit and gave satisfying feedback on the reliability and road safety educability of the VR kit evaluation survey. Performance analysis shows that the VR kit can perform well with an average framerate of 23 FPS. In conclusion, the VR Learning Kit for Road Crossing Safety project successfully developed a comprehensive VR solution that offers an immersive and engaging learning experience